Rights, Social Trauma and Restitution. Synchronicity and Unity: the case of Uruguay (Andamios, Revista de Investigación Social, 2012)
This paper assesses the ability of reborn democracies after State Terror to reinstate rights in all their integrity and synchronicity. Under a historical approach, with an emphasis on the Uruguayan case, it analyses the difficulties of reincorporating the judicial framework and the diverse sensitivities of the international environment of Human Rights in order to achieve the full reestablishment of institutionalism. It privileges the current phase in order to show how some Latin American States are prone to select rights by their content and temporality. Even though the value system surrounding rights is indeed a part of the global agenda, the framework of its definition is national. The Uruguayan debate is substantiated in two regionally neighboring models, Argentina and Brazil, with opposite approaches for the addressing of the challenges that their traumatic pasts impose on the present. In between them, Uruguay builds a laborious path.
Keywords: Human rights; Uruguay; reincorporation of rights; law nullifying the state’s claim to punish certain crimes; democracy